Buffer-Stock Saving and the Life Cycle/Permanent Income Hypothesis - Carroll, C. D. (Quarterly Journal of Economics, 1997)
This paper argues that the typical household's saving is better described by a “buffer-stock” version than by the traditional version of the Life Cycle/Permanent Income Hypothesis (LC/PIH) model. Buffer-stock behavior emerges if consumers with important income uncertainty are sufficiently impatient. In the traditional model, consumption growth is determined solely by tastes. In contrast, buffer-stock consumers set average consumption growth equal to average labor income growth, regardless of tastes. The model can explain three empirical puzzles: the “consumption/income parallel” documented by Carroll and Summers; the “consumption/income divergence” first documented in the 1930s; and the stability of the household age/wealth profile over time despite the unpredictability of idiosyncratic wealth changes.